A study on the correlation between the prognosis of HPV infection and lesion recurrence after cervical conization - Lu, Junling; Han, Shichao; Li, Ya; Na, Jing; Wang, Jun (Frontiers in Microbiology, 2023)
Introduction: Persistent human papillomavirus infection is an important factor in the development of cervical cancer, which is usually a long process evolving from the development of squamous intraepithelial lesions (SIL), also referred to as cervical intraepithelial neoplasia (CIN). Local treatment of advanced squamous intraepithelial lesions, also regarded as High-Grade Squamous Intraepithelial Lesion, may be effective in preventing cancer. Objective: To promptly identify high-risk patients with a tendency to recurrence. Methods: We retrospectively analyzed the clinical data of 300 patients with high-grade squamous intraepithelial lesions of the cervix admitted to the Second Affiliated Hospital of Dalian Medical University from 2019 to 2020 to investigate the relationship between recurrence of cervical lesions and postoperative regression of HPV infection, as well as other related risk factors. Results: We found that the HPV-negative rates were 81.81%, 85.71%, and 90.91% at 6, 12, and 24 months, respectively, and the average lesion recurrence rate was 8.16%, with a median time to recurrence of 14 months in patients undergoing CKC for HSIL. The risk of cervical squamous intraepithelial lesions was highest in patients with HPV16.Patients over 61 years of age had the lowest postoperative HPV-negative rate. The conversion rate was significantly lower in patients with multiple HPV genotypes than in those with single HPV infection (P<0.05). The probability of recurrence was higher in patients with the same HPV infection genotype before and after surgery than in patients with different infection genotypes before and after surgery (P<0.05). Conclusion: Combined with the literature review, we believe that patients aged ≥50 years, with ≥3 pregnancies and births, a history of smoking, and consistent genotypes of preoperative and postoperative HPV infection in cervical conization have more HPV re-infection or persistent infection, and that these factors may be high-risk factors for lesion recurrence. For patients with possible potential high-risk factors, we need to carry out individualized follow-up and focused management, take timely and effective management measures, optimize the treatment plan, reduce the recurrence rate, prevent HSIL and cervical cancer, improve the quality of patient's survival and improve the prognosis.